Mode deactivation therapy on attitude towards psychological help-seeking among students with low achievement Motivation in secondary schools in Idemili North, Nigeria (2017)
Attitudinal barriers have consistently been related to actual utilization of services. This study investigated the effectiveness of Mode Deactivation Therapy (MDT) on modifying attitude towards psychological help seeking among students in Idemili North, Nigeria (IDNLG). Pre-test post test quasi experimental design with 2x 2 factorial matrix was utilized. The population of the study is all Senior Secondary School one (SS) students spread across 16 schools located within IDNLG. Eighty-five students (Female=44; male=41) with age range of 13-19 years (x =13.3SD=3.7) who obtained less than 30 in the Achievement Motivation Inventory participated in study. They were randomized into experimental and control Group. The experimental group was treated with MDT for 7 weeks which lasted for 2hrs per week while the control group was used as a comparison group. The outcome measure was Attitude towards seeking psychological help (Fischer & Turner, 1970).